'Informal activity' in mathematics instruction - Christiansen, Iben Maj (NOMAD Nordic Studies in Mathematics Education, 1994)
On the basis of an analysis of portions of a modelling course in Danish high school, the existence of 'informal activity' is asserted. This activity can contain reflections on the mathematical activity performed when 'on task', but also allows the students to distance themselves from the content and school-tasks in gene- ral. Informal activity may thereby contain a potential for critique which is not rea- lized due to isolation in the informal activity. To give insight on the possibility for change, the formation of discourses and their relation to the setting is discussed.